Plan de promoción y publicidad del almacén Olguita, de la ciudad de Quevedo, año 2014 - Cadena Alvarado, Alexandra Katherine (2013)
The study carried out in the facilities of store Olguita, located in Mexico # 200 and Juan Montalvo, parroquia San Camilo, Quevedo canton, province of Los Ríos, with the purpose of work a plan of promotion and advertising that allow enterprise to position itself in the market of the canton and its adjacent sectors. Ran a market research in the sector where the pharmacy is located to its effect was implemented a study of field, through surveys aimed at 226 potential clients and 177 customers store, allowing you to assess the level of satisfaction and positioning of the business in the local market, similarly identified items for the home are sold more. The store Olguita presents advantages in their forts that have kept it stable in the local market, including the wide variety of items for the home that offers, low prices, brands and the cordial attention, but at the same time presents weaknesses that are negatively affecting business development and positioning of the business, as insufficient advertising and corporate store image. At the present time business goes through several drawbacks, among them; the poor knowledge about the market segment, advertising and lack of promotion, these difficulties have resulted in sales will not increase and customers to address to other shops in the surrounding area. The absence of a plan for promotion and advertising in the warehouse Olguita has influenced the positioning of the business in the local market, has also impacted negatively on business development and increase the customer base, which is why it is necessary to design this plan, which provide tools for enhancement and growth for business and thus link it with the environment of the market to which it is directed. Within this argument the plan takes on vital importance for the survival of the company, since it transmits information about its products and its corporate image to customers; also allows you to meet the needs of consumers and the reaction that they have with their product. The purpose of this study was to design a new image of the Olguita store and let you know the population which Quevedo, has increased in the canton through new communication strategies and advertising, in order to attract new customers that contribute to the growth of the company. It is important that the company implement new ways to satisfy the customer, more than cordial attention, it is necessary to apply seductive promotions to attract more customers, such as special discounts on purchases, offer combos and give gifts surprises.